2012
DOI: 10.1016/j.pain.2012.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Intact 2D-form recognition despite impaired tactile spatial acuity in complex regional pain syndrome type I

Abstract: Tactile acuity measured by 2-point discrimination performance is impaired in patients with complex regional pain syndrome type I (CRPS-I). This is mirrored by pain-associated shrinkage of the cortical representation of the affected limb. We investigated whether, also, more complex tactile performance assessed by a dynamic 2D-form perception task is disturbed in CRPS-I patients. Therefore, we developed a Braille-like recognition task (BT) for geometrical dot pattern identification by dynamic touch. We studied 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
8
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 67 publications
4
8
0
2
Order By: Relevance
“…Although our data have yet to be supported by imaging results and interpretation should hence be made tentatively, it may be hypothesized that the integration of multimodal percepts in association areas such as the ventral premotor cortex or posterior parietal region is unaffected in CRPS, the retained illusion strength suggesting similar functionality to that of healthy subjects and patients with upper limb pain of other origin. In line with this notion, Reiswich et al [51] reported preserved 2-dimensional form recognition abilities in CRPS patients, indicating intact higher order sensory integration, despite impaired tactile acuity (corresponding to S1 and SII function). Moreover, Moseley and Wiech [40] also observed intact visuotactile integration despite impaired tactile discrimination in CRPS patients.…”
Section: Intact Ability To Perceive Illusory Ownershipmentioning
confidence: 77%
See 2 more Smart Citations
“…Although our data have yet to be supported by imaging results and interpretation should hence be made tentatively, it may be hypothesized that the integration of multimodal percepts in association areas such as the ventral premotor cortex or posterior parietal region is unaffected in CRPS, the retained illusion strength suggesting similar functionality to that of healthy subjects and patients with upper limb pain of other origin. In line with this notion, Reiswich et al [51] reported preserved 2-dimensional form recognition abilities in CRPS patients, indicating intact higher order sensory integration, despite impaired tactile acuity (corresponding to S1 and SII function). Moreover, Moseley and Wiech [40] also observed intact visuotactile integration despite impaired tactile discrimination in CRPS patients.…”
Section: Intact Ability To Perceive Illusory Ownershipmentioning
confidence: 77%
“…At the same time, recent findings indicate that despite dysfunctional sensory processing, integration of body-related multisensory perceptions is intact in CRPS [40,51,64]. For example, despite decreased tactile spatial acuity, CRPS patients present intact 2-dimensional form-recognition abilities, provided that the form is above the spatial resolution performance [51]. Moreover, visuotactile integration was shown to be unaffected when CRPS patients underwent tactile training while simultaneously watching their healthy hand [40].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…42,[47][48][49] This is clinically seen by an increase in the two-point discrimination threshold in the affected region. 50 In addition, correlations between tactile discrimination and cortical representation on the somatosensory cortex have been identified, 43 showing changes in representation in the sensory homunculus in persistent pain.…”
Section: Two-point Discriminationmentioning
confidence: 99%
“…Interessanterweise fand sich eine bilaterale kortikale Disinhibition nach Doppelpuls-SEP-Reizung[ 15 ] . In einer neuen Studie wurde auch der Befund der erhöhten Zweipunktdiskriminationsschwelle reproduziert[ 16 ] . Zudem zeigte sich, dass diese Störung bei Patienten mit dystonen Symptomen stärker ausgeprägt war als bei sonstigen CRPS-Patienten[ 10 ] .…”
unclassified